METABOLIC FACTORS AND CARDIOVASCULAR RISK: INSIGHTS FROM A RETROSPECTIVE COHORT STUDY - Moiud Mohyeldin (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD Risk Factors Background: Cardiovascular disease remains a leading cause of morbidity and mortality worldwide. Identifying modifiable risk factors is crucial for risk stratification and prevention strategies. This study aimed to investigate the association between various metabolic parameters and the occurrence of cardiovascular events in a cohort of patients, with the goal of informing targeted interventions and risk assessment approaches. Methods: We conducted a retrospective analysis of 190 patients, evaluating the impact of metabolic equivalents (METs), history of chronic kidney disease (CKD), diabetes mellitus (DM), hyperlipidemia (HLD), hypertension (HTN), body mass index (BMI), and mean pulmonary hypertension resistance (MPHR) on the incidence of cardiac events, including myocardial infarction, unstable angina, and cardiac death. Logistic regression models were employed to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Chi-square tests and tests for equality of variances were performed to assess statistical significance. Results: Patients with METs >8 had a higher incidence of cardiac events compared to those with METs ≤5 (56.3% vs. 12.5%, p=0.032). DM (46.9% vs. 22.2%, p=0.0026) and HTN (87.5% vs. 67.7%, p=0.0212) were also significantly associated with cardiac events. Mean BMI was higher in the cardiac event group (31.87 vs. 29.30, p=0.0168). After adjusting for confounders, the OR for METs >8 was 1.82 (95% CI 0.51-6.46, p=0.36). No significant associations were observed for HLD, CKD, family history of coronary artery disease, or peripheral vascular disease. Conclusions: Our findings underscore the importance of metabolic factors, particularly METs levels, DM, and HTN, in predicting cardiovascular risk. Elevated BMI was also associated with increased event occurrence. These results highlight the need for comprehensive management of metabolic disorders to mitigate cardiovascular disease burden. Future studies should explore targeted interventions and risk assessment strategies incorporating these metabolic parameters to optimize cardiovascular disease prevention and management.